Viewing Microorganisms through the Lenses of Realism - Adhikari, Abhaya Shekhar (Tribhuvan University Journal, 2020)
The pandemic created by the Corona virus and the history of biological events have brought to the fore some sort of relation between microorganisms and state affairs. This relationship has been studied through the perspective of the realism theory of international relations. This exploratory qualitative research employed data from various literatures and assessed those data to establish a link between them. The research has confirmed that security is a link between microorganisms and realism. Microorganisms affect human health, society and state affairs and create economic and political chaos. This anomaly in state affairs is seen to jeopardize a state’s security. It is established that microorganisms possess a threat for survival of the state by putting the cores of state security in peril. This research suggests that actions against these threats is a priority obligation for all states to fulfil.